TOPONYMIC MATERIAL RECOVERY OF PERU, DR. JAVIER PULGAR VIDAL LEGACY - Comeca Chuquipul, Miguel (2014)
Nowadays, still persists unawareness of the original meaning of the names of different places of our territory, many of them have official names which are reflected in cartography; however in many cases the local population recognize it with another denomination. The science that studies the place names is toponymic as defined by. Dr. Pulgar Vidal, the same person who also dedicated much of his life to the study of places and natural regions of Peru, the product of this work has left a considerable material, reflected in documents, files, clippings, still slopes to be completed. With this research was achieved retrieve, sort, systematize in an initial way the existing valuable material in the toponymyc background of the Professional School of Geography of UNMSM, created by Dr. Javier Pulgar Vidal, with the purpose of make available to national scientific community, international, governmental and non-governmental institutions, in the perspective that the names of the various places, are those that reflect their true meaning for the purpose of preserve our rich geographical, historical, and cultural heritage.